2014
DOI: 10.1111/ans.12783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous lignocaine on perioperative stress response and post‐surgical ileus in elective open abdominal surgeries: a double‐blind randomized controlled trial

Abstract: Perioperative i.v. lignocaine infusion attenuates the operative stress response, provides effective analgesia and reduces the need for opioids post-operatively. Through these effects, it reduces post-operative ileus and the incidence of PONV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“… 56 In one study analyzing the effect of intravenous lignocaine given intraoperatively, they reported a reduction in postoperative analgesic requirements as well as improved time to flatus and reduced postoperative nausea and vomiting. 28 As previously stated, there is little reported evidence on the effects of different analgesic methods on the systemic inflammatory response following colorectal surgery. One study reported that those receiving intravenous lignocaine had lower postoperative levels of both CRP and IL-6 following major abdominal surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 56 In one study analyzing the effect of intravenous lignocaine given intraoperatively, they reported a reduction in postoperative analgesic requirements as well as improved time to flatus and reduced postoperative nausea and vomiting. 28 As previously stated, there is little reported evidence on the effects of different analgesic methods on the systemic inflammatory response following colorectal surgery. One study reported that those receiving intravenous lignocaine had lower postoperative levels of both CRP and IL-6 following major abdominal surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 summarizes the included studies for each ERAS component and the marker of the SIR analyzed. 10 28 Evidence relating to other outcomes of ERAS programmes such as length of stay or postoperative complications were obtained from the most recent Cochrane Reviews or meta-analyses on the specific topic. Meta-analysis of included studies was not performed because of significant heterogeneity among study methodology, populations, and outcomes measured.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 summarizes the included studies for each ERAS component and the marker of the SIR analyzed. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Evidence relating to other outcomes of ERAS programmes such as length of stay or postoperative complications were obtained from the most recent Cochrane Reviews or meta-analyses on the specific topic. Metaanalysis of included studies was not performed because of significant heterogeneity among study methodology, populations, and outcomes measured.…”
Section: Methodsmentioning
confidence: 99%
“…It has several beneficial effects apart from reducing opioid requirements (by up to two-thirds): there is a reduced duration of PONV, ileus, and hospital stay. 41,42 In addition, there are other systemic effects, such as reduced stress response as measured by total leukocyte count, C-reactive protein, and interleukin-6 (IL-6), 43 and possibly an anticancer effect too. 44 Many of these effects seem to be more marked for open surgery.…”
Section: Intravenous Lidocainementioning
confidence: 99%